2023
DOI: 10.3390/su15064824
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Flexural Capacity Prediction of Corroded RC Beams with an Efficient and User-Friendly Tool

Abstract: Steel corrosion poses a serious threat to the structural performance of reinforced concrete (RC) structures. Thus, this study evaluates the flexural capacity of RC beams through machine learning (ML)-based techniques with six parameters used as input features: beam width, beam effective depth, concrete compressive strength, reinforcement ratio, reinforcement yield strength, and corrosion level. Four single and ensemble ML models are evaluated; namely, decision tree, support vector machine, adaptive boosting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The performance of optimized ML models was evaluated using multiple statistical metrics such as root mean squared error (RMSE), mean absolute error (MAE), mean absolute percentage error (MAPE), coefficient of determination R 2 , scatter index (SI), and performance index (PI) (see Table 2). Many researchers utilized these indices to evaluate the predictive performance of different ML models [53][54][55][56][57][58][59][60]. The RMSE measures the average magnitude of the errors between the predicted and actual values, indicating the model's predictive accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of optimized ML models was evaluated using multiple statistical metrics such as root mean squared error (RMSE), mean absolute error (MAE), mean absolute percentage error (MAPE), coefficient of determination R 2 , scatter index (SI), and performance index (PI) (see Table 2). Many researchers utilized these indices to evaluate the predictive performance of different ML models [53][54][55][56][57][58][59][60]. The RMSE measures the average magnitude of the errors between the predicted and actual values, indicating the model's predictive accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…, 2020; Jnaid and Aboutaha, 2016), neural network (Imam et al. , 2015), or machine learning-based techniques (Abushanab et al. , 2023; Alabduljabbar et al.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of references is available in the literature that provides reliable methods for estimating the flexural capacity of RC beams under chloride attack. Previous studies have employed finite element analysis (Castorena-Gonz alez et al, 2020;Jnaid and Aboutaha, 2016), neural network (Imam et al, 2015), or machine learning-based techniques (Abushanab et al, 2023;Alabduljabbar et al, 2020), which, despite their impressive predictive accuracy, are complicated and expensive. Perhaps, the simplest approach is to employ a single empirical factor (also called corrosion coefficient) that serves as a multiplier to the moment capacity to correct for the effect of corrosion.…”
mentioning
confidence: 99%
“…They found that using two hidden layers and 20 neurons provided the most accurate prediction value. In a recent study conducted by Abushanab A. et al (2023) [39], the flexural strength of reinforced concrete beams was evaluated using machine learning (ML) techniques. Various models, including SVM, DT, ADB, and GB, were employed for analysis.…”
Section: Introductionmentioning
confidence: 99%